Peningkatan Literasi Digital Bagi Guru SD Negeri 132408 Kota Tanjungbalai Dalam Mencegah Dan Mengatasi Cybercrime - Siregar, Iqbal Kamil; Endra Saputra (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: The rapid development of digital technology in education presents significant benefits, but it also introduces serious challenges in the form of increasing threats of Cybercrime. Teachers at SD Negeri 132408 Kota Tanjungbalai, as the frontline of education, often lack an adequate understanding of digital literacy and how to handle cybercrimes, such as the spread of false information, data theft, and violations of digital ethics. This community service activity aims to enhance the digital literacy capacity of teachers in preventing and addressing Cybercrime within the school environment. The methods used include intensive training, group discussions, case studies, and practical simulations, implemented in three stages: preparation, implementation, and evaluation. The solutions offered encompass providing digital literacy materials, Cybercrime prevention training, and developing practical guidelines. Evaluation results show that teacher understanding increased significantly, with the average score rising from 45 to 78 (p<0.05). The targeted outputs of this activity are the publication of a scientific article in a Sinta 5 accredited national journal as a mandatory output, and a popular article in mass media as an additional output. This activity is expected to increase teachers' awareness and skills in creating a safe and healthy digital education environment. Keywords: cybercrime; digital literacy; education; elementary school teachers; training Abstrak: Pesatnya perkembangan teknologi digital di dunia pendidikan menghadirkan manfaat besar, namun juga memunculkan tantangan serius berupa meningkatnya ancaman Cybercrime. Guru di SD Negeri 132408 Kota Tanjungbalai, sebagai garda terdepan pendidikan, seringkali belum memiliki pemahaman yang memadai tentang literasi digital dan cara menghadapi kejahatan siber, seperti penyebaran informasi palsu, pencurian data, dan pelanggaran etika digital. Kegiatan pengabdian ini bertujuan untuk meningkatkan kapasitas literasi digital guru dalam mencegah dan mengatasi Cybercrime di lingkungan sekolah. Metode yang digunakan berupa pelatihan intensif, diskusi kelompok, studi kasus, dan simulasi praktik, yang dilaksanakan dalam tiga tahap: persiapan, pelaksanaan, dan evaluasi. Solusi yang ditawarkan mencakup pemberian materi literasi digital, pelatihan pencegahan Cybercrime, dan penyusunan panduan praktis. Hasil evaluasi menunjukkan pemahaman guru meningkat signifikan dari skor rata-rata 45 menjadi 78 (p<0.05). Target luaran dari kegiatan ini adalah publikasi artikel ilmiah pada jurnal nasional terakreditasi Sinta 5 sebagai luaran wajib, dan artikel di media massa sebagai luaran tambahan. Diharapkan kegiatan ini mampu meningkatkan kesadaran dan keterampilan guru dalam menciptakan lingkungan pendidikan digital yang aman dan sehat. Kata kunci: cybercrime; guru sd; literasi digital; pelatihan; pendidikan